2020
DOI: 10.1371/journal.pone.0237259
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of spent mushroom substrate: Utilization as feed material for the larvae of the yellow mealworm Tenebrio molitor (Coleoptera: Tenebrionidae)

Abstract: Spent mushroom substrate is made from the waste remaining after the harvest of mushrooms. Here, we evaluated the potential of five spent edible fungi (Auricularia cornea, Lentinus edodes, Pleurotus eryngii, P. citrinopileatus and P. ostreatus) substrates as feed sources for Tenebrio molitor larvae. Young larvae did not survive on any substrate except the spent L. edodes substrate (36.7%). The survival rates in young larvae were similar among the different diets in which wheat bran or rice bran was replaced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The balancing of the protein and carbohydrate content, with incomplete nutrition, was proven in locusts ( Locusta migratoria L., Orthoptera: Acrididae) [ 5 ]. Different studies have examined the use of agricultural by-products [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], fish discards [ 13 ] and organic waste [ 14 ] as insect food and the effects on larval chemical composition. Researchers concluded that it is possible to rear mealworm larvae on food by-products.…”
Section: Introductionmentioning
confidence: 99%
“…The balancing of the protein and carbohydrate content, with incomplete nutrition, was proven in locusts ( Locusta migratoria L., Orthoptera: Acrididae) [ 5 ]. Different studies have examined the use of agricultural by-products [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], fish discards [ 13 ] and organic waste [ 14 ] as insect food and the effects on larval chemical composition. Researchers concluded that it is possible to rear mealworm larvae on food by-products.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important aspects of mass production involves the formulation of inexpensive yet effective diets that maximize biomass productivity over time. Recent research has focused on the potential use of agricultural by-products as insect food to reduce production costs of insect biomass [16][17][18][19]. However, current studies on T. molitor have focused on the effects of single ingredients on biological and food utilization parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The larval developmental stages of T. molitor could vary from nine to more than 20 instars, depending on rearing conditions, 56 but most of them developed in 13–16 instars 57,58 and sold at these stages at only about $2–3 per kilogram. When the environmental cost is also taken into account, the advantages of using T. molitor are even more obvious, because A. pernyi larvae feed on the leaves of Quercus , 20 while T. molitor could even be reared on agricultural organic wastes 59 . This would not only reduce production cost but also make it available in all seasons 37 .…”
Section: Discussionmentioning
confidence: 99%